2009
DOI: 10.1016/j.exer.2009.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine-O-sulfation in the retina

Abstract: Tyrosine-O-sulfation, a post-translational modification, is catalyzed by two independent tyrosylprotein sulfotransferases (TPSTs). As an initial step towards understanding the role of TPSTs in retinal function, this study was undertaken to determine the extent to which tyrosine-O-sulfation of proteins is utilized in the retina. A previously characterized anti-sulfotyrosine antibody was used to determine the presence and localization of tyrosine-O-sulfated proteins (TOSPs) in the retina. Using Western blot, RT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 36 publications
3
38
0
Order By: Relevance
“…We have previously shown that transcripts for both Tpst1 and Tpst2 are expressed in human and mouse retina [8]. Both transcripts are expressed in the mouse retina as early as P1, although transcript levels fluctuate over the course of retinal development [10].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that transcripts for both Tpst1 and Tpst2 are expressed in human and mouse retina [8]. Both transcripts are expressed in the mouse retina as early as P1, although transcript levels fluctuate over the course of retinal development [10].…”
Section: Resultsmentioning
confidence: 99%
“…The sources of IPM proteins are the retina and the RPE. 6 For simplicity, henceforth the use of the abbreviation ECM covers both.…”
Section: Retinal Extracellular Matrixmentioning
confidence: 99%
“…Protein was estimated, fractionated, and transferred to membranes and immunoblotted as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
“…For immunoprecipitation, 500 g of protein extracts were incubated with the desired antibody for 12 h, precipitated by centrifugation, eluted in 1ϫ Laemmli buffer (33), and fractionated by SDS-PAGE as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation